Evaluation of anti-rabies vaccination and supplementation with probiotic in the humoral immune response in cattle - Ferreira, Luciene Aparecida; Pardo, Paulo Eduardo; Frazatti-Gallina, Neuza Maria; Mourão-Fuches, Regina Maria; Ventini, Daniella Cristina; Do Nascimento Kronka, Sérgio; Arenas, Sandro Eduardo; De Souza Reis, Luis Souza Lima [UNESP] (Universidade Estadual de Londrina, 2009)
This study evaluated the humoral immune response of a new rabies vaccine developed by the Instituto Butantan (potency of 3.27 UI/ml) in primovaccinated cattle and the effect of probiotic on this response. Thirty-four 15-month old Nelore cattle were randomly divided into 2 groups (17 animals/group). All the animals were vaccinated on day 0 (zero) and then animals in one group received probiotic added to a mineral mixture (GP) while the others were given only the mineral mixture (GC). Blood samples were collected on days 0, 75 and 150 for rabies neutralizing antibodies titers by seroneutralization assay on BHK 21 cells (RFFIT). Protective antibody titers (≥0.5 UI/mL) were found in 82.4% of the animals from GP and in 76.5% of the animals from GC and no statistical difference (p>0.05) between antibody titers in GP and GC was detected on days 75 and 150. It was also observed that in both groups antibody titers was decreased on day 150 (p<0.01). In conclusion, the tested rabies vaccine promotes efficient soroconversion and keeps antibody levels in primovaccinated cattle, but probiotic does not affect the humoral anti-rabies immune response.
Avaliação da vacinação anti-rábica e da suplementação com probiótico na resposta imune humoral em bovinos
Keywords: Antibodies; Cattle; Humoral immune response; Probiotic; Rabies vaccination